Alauda arvensis subsp. weigoldi Hartert ... - LeCROY, M. A. R. Y. (Zenodo, 2003)
Alauda arvensis weigoldi Hartert Alauda arvensis weigoldi Hartert, 1922a: 20 (Hankóu). Now Alauda gulgula weigoldi Hartert, 1922. See Cheng, 1987: 425, Robson, 2000: 476, and Dickinson et al., 2001a: 93. HOLOTYPE: AMNH 555616, adult male, collected at Hank’ou, 30°35′N, 114°19′E (Times Atlas), Hubei, China, on 18 March 1912, by Admiral Hubert Lynes (no. 1854). From the Rothschild Collection. COMMENTS: This holotype is the only specimen collected by Admiral Lynes at Hank’ou on this date (cited in the original description). His other specimens from Hank’ou, collected in March, April, and May 1912, are paratypes: AMNH 555617–555624. ... : Published as part of LeCROY, M. A. R. Y., 2003, TYPE SPECIMENS OF BIRDS IN THE AMERICAN MUSEUM OF NATURAL HISTORY. PART 5. PASSERIFORMES: ALAUDIDAE, HIRUNDINIDAE, MOTACILLIDAE, CAMPEPHAGIDAE, PYCNONOTIDAE, IRENIDAE, LANIIDAE, VANGIDAE, BOMBYCILLIDAE, DULIDAE, CINCLIDAE, TROGLODYTIDAE, AND MIMIDAE, pp. 1-156 in Bulletin of the American Museum of Natural History 278 (278) on pages 28-29, DOI: 10.1206/0003-0090(2003)278<0001:tsobit>2.0.co;2, http://zenodo.org/record/13256611 ...